Contextual analysis of fragmentation of the anthropomorphic figurines from the Late Neolithic site of Selevac - Marko Porčić (Etnoantropološki Problemi, 2016)
The biographical approach to material culture and the hypothesis of deliberate fragmentation of anthropomorphic figurines are used in this paper to deduce a hypothesis that there should be an association between particular fragmentation categories and context types in the archaeological record of the Late Neolithic settlements in Central Balkans. This hypothesis is tested using published data from the site of Selevac by performing correspondence analysis and chi-square test on a contingency table in which categories of fragmentation are cross-tabulated with context types. The results are statistically significant, suggesting that complete figurines are associated with houses while transversely broken figurines are associated with pits. There is also evidence that figurines were broken differentially in respect to their original size.